Analisis Kelayakan Pengembangan Unit Hemodialisis di Rumah Sakit X di Surabaya - Anita Dahliana; Winnie Nirmala Santosa; Ummy Maisarah Rasyidah (Keluwih: Jurnal Kesehatan dan Kedokteran, 2022)
Abstract—Indonesia is one country with the kidney failure is quite high, according to the Indonesian Society of Nephrology (PERNEFRI) in the 5th Report of Indonesian Renal Registry, in 2012 there were 16.040 patients with kidney failure but reportedly only 9161 patients were active in hemodialysis in 2012. The increasing incidence of kidney failure that requires hemodialysis services, the more hemodialysis services are needed to meet the needs of patients with kidney failure. Research to assess the development of hemodialysis units at Wiyung Sejahtera Hospital in terms of the size of the market difference, the difference in the cost of single-use and reuse HD units compared to the amount of financing from BPJS. The research method uses a case study conducted at Wiyung Sejahtera Hospital. Data collection is done by means of observation, document study and interviews. The investment analysis method used is the Net Present Value method, the Pay Back Period method and the Internal Rate of Return. Results and Discussion. The results of the SWOT analysis of the hospital are in quadrant I, where the hospital has a great opportunity to increase the number of hemodialysis services. The results of the financial analysis and investment assessment, Wiyung Sejahtera Hospital has a profitable income growth and based on the results of the analysis the investment is relatively safe. Keywords: feasibility study, hemodialysis, SWOT analysis Abstrak—Indonesia merupakan salah satu negara dengan angka gagal ginjal cukup tinggi. Perkumpulan Nefrologi Indonesia (PERNEFRI) dalam 5 th Report of Indonesian Renal Registry pada tahun 2012 melaporkan terdapat 16.040 penderita gagal ginjal, tetapi hanya 9.161 pasien yang aktif dalam kegiatan hemodialisa. Meningkatnya insiden gagal ginjal yang memerlukan pelayanan hemodialisa, maka semakin banyak senter pelayanan hemodialisa yang diperlukan untuk memenuhi kebutuhan terhadap pasien gagal ginjal. Tujuan penelitian untuk menilai kelayakan pengembangan unit hemodialisa di RS Wiyung Sejahtera ditinjau dari besarnya pangsa pasar, selisih biaya unit cost HD single use dan reuse dibandingkan dengan besarnya pembiayaan dari BPJS. Metode penelitian menggunakan studi kasus yang dilakukan di RS Wiyung Sejahtera. Pengumpulan data yang dilakukan dengan cara observasi, studi dokumen dan wawancara. Metode analisis investasi yang digunakan adalah metode Net Present Value, metode Pay Back Periode dan Internal Rate of Return. Hasil dan pembahasan. Hasil analisis SWOT RS berada pada kuadran I, dimana RS mempunyai peluang besar meningkatkan jumlah layanan hemodialisa. Hasil analisis keuangan dan penilaian investasi, RS Wiyung Sejahtera memiliki perkembangan pendapatan yang menguntungan dan berdasarkan hasil analiisis investasi relatif aman. Kata kunci: studi kelayakan, hemodialisis, analisis SWOT